GENESIS AND EVOLUTION OF THE CONCEPT OF «WORK» - GRITSENKO, Andrii; CHATCHENKO, Taras (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the genesis of the concept of ‘work’. The main stages of development of this concept are described. The author identifies current trends in the context of the global COVID-19 epidemic. The author traces the growing understanding of labour as the basis of value from ancient Greek authors to classical political economy and Karl Marx, and then traces the further decline of this theory in neoclassical economics. While the ancient Greeks did not have a concept of labour as a measure of value, scholastic authors established the idea that labour and production costs determine value. Labour took centre stage with Adam Smith, but a full-fledged labour theory of value was achieved thanks to David Ricardo. Marx added a philosophical dimension to the concept by linking it to a critique of classical political economy. The labour theory of value was attacked in neoclassical formulations that eventually led to the analytical disappearance of labour in several ways. Labour became just another factor of production, with marginal productivity governing its price. Then, factors of production and final goods became analytically equivalent as sources of subjective utility, especially in the context of general equilibrium theory. In disjunctive models of labour supply, labour was replaced by its absence, ‘leisure’. It has been found that work has different meanings for different people, but for ease of understanding and for the purpose of analysis, the meaning of work has been classified into two broad categories - the social meaning of work and the personal meaning of work. When the main function of a job is to fulfil social and economic expectations, a person can be said to have social job meaning. If work is primarily a means of satisfying personal aspirations and interests, then it has personal meaning. The narratives suggest that when people have several career or job options to choose from, and are clear about their interests, their job choices are driven by personal inclinations, and work becomes personally meaningful. On the other hand, when the number of job options is limited and a person does not have a clear idea of their own interests, social expectations and metaphors related to work influence the meaning of work and job choice.
Keywords: work; physical labour; self-employment; labour force; remote work